Modeling population dynamics of yeast-like symbionts (Ascomycota: Pyrenomycetes: Clavicipitaceae) of the planthopper Delphacodes kuscheli (Hemiptera: Delphacidae) - Liljesthröm, Gerardo G. (2016)
Fil: Liljesthröm, Gerardo G.. Centro de Estudios en Parasitología y Vectores (CEPAVE). Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina